Straight‐to‐test colonoscopy for 2‐week‐wait referrals improves time to diagnosis of colorectal cancer and is feasible in a high‐volume unit. (5th September 2017) - Banerjea, A.; Voll, J.; Chowdhury, A.; Siddika, A.; Thomson, S.; Briggs, R.; Humes, D. J.; ,
Abstract: Aim: We have introduced 'straight‐to‐test' (STT) colonoscopy as part of our 2‐week‐wait (2WW) pathway to address increasing numbers of urgent referrals for colorectal cancer (CRC) within the National Health Service. In this study we evaluated the ability of this initiative to shorten the time to diagnosis of CRC. Method: We amended our 2WW referral form to include performance status and comorbidities. General practitioners were asked to provide data on estimated glomerular filtration rate and full blood count/ferritin. Our 2WW referrals were screened by a colorectal consultant and a nurse specialist. Those deemed unsuitable for STT were offered outpatient assessment (OPA). Results: Of 553 2WW referrals screened, 352 were considered suitable, 65 of whom failed a telephone assessment or were uncontactable, and accordingly 287 were offered the STT pathway. The STT group was significantly younger than the OPA group (median 65.9 years vs 78.7 years; P  < 0.0001). STT colonoscopy significantly reduced the time to first test (13 days vs 22 days; P  < 0.0001) and tissue diagnosis from the referral date (17 days vs 24.5 days; P  < 0.0001). Thirty‐seven (6.8%) CRCs were detected. Proportionately fewer patients in the STT pathway were managed with 'best supportive care only' compared with patients attending OPA (one of 15 vs six of 22, respectively). STT colonoscopy obviated the need for clinic attendance before testing in 287 patients, representing a potential net cost benefit of at least £48 500 in 4 months. Conclusion: STT colonoscopy was safe and effective for selecting out a group of symptomatic patients who could proceed straight to endoscopic examination and receive a diagnosis more rapidly.